Budidaya Ikan Kerapu (Epinephelus tauvina Forsskal, 1775) dan Ikan Beronang (Siganus canaliculatus Park, 1797) dalam Karamba Jaring Apung dengan Sistim Polikultur - Paruntu, Carolus Paulus (Universitas Sam Ratulangi, 2015)
The aim of the present research was to evaluate the daily growth ratio, food conversion ratio and mortality of grouper (Epinephelus tauvina) and rabbit fish (Siganus canaliculatus) in floating net with polyculture system. This experiment was done at the coastal area of Tomini Bay in the North Sulawesi Province. The observations were done every two weeks for three months from August - November 2014. Twenty five groupers (62.41 grams in ABWo) and twenty five rabbit fish (52.2 grams in ABWo) were used for polyculture experiment, while fifty groupers (56.71 grams in ABWo) for monoculture. The results indicated that the daily individual growth of Epinephelus tauvina on polyculture was 1.29%, with food conversion ratio 6.1, while it on monoculture was 1,18%, with food conversion ratio 6.4. The daily individual growth of Siganus canaliculatus on polyculture was 0,8%, with food conversion ratio 3.8. Mortality for all species studied were 0%. The present research showed that the polyculture system was better than monoculture system. The future studies suggest that the polyculture system in the floating net may be developed and applied as a mariculture model in the North Sulawesi Province for prosperous life of fisherman. Keywords: Epinephelus tauvina, Siganus canaliculatus, polyculture system, floating net, prosperous life, fisherman.